Cytosolic d‐type CpG‐oligonucleotides induce a type I interferon response by activating the cGAS‐STING signaling pathway. Issue 7 (12th May 2021) - Bode, Christian; Poth, Jens M.; Fox, Mario; Schulz, Susanne; Klinman, Dennis M.; Latz, Eicke; Steinhagen, Folkert
Abstract: Cytosolic DNA receptor cyclic GMP‐AMP (cGAMP) synthase (cGAS) has been shown to be critically involved in the detection of cytosolic, self‐ and non‐self‐DNA, initiating a type I IFN response through the adaptor protein Stimulator of Interferon Genes (STING) and interferon regulatory factor 3 (IRF3). Current studies propose that canonical binding of dsDNA by cGAS depends on DNA length, but not on base sequence. In contrast, activation of TLR9 is sequence dependent. It requires unmethylated CpG dinucleotides in microbial DNA, which is mimicked by synthetic oligodeoxynucleotides (ODN). Here, we provide evidence that d ‐type ODN (D‐ODN), but not K‐type ODN (K‐ODN), bind to human cGAS and activate downstream signaling. Transfection of D‐ODN into a TLR9‐deficient, human monocytic cell line (THP‐1) induced phosphorylation of IRF3 and secretion of IFN. This response was absent in cells with CRISPR/Cas9‐mediated cGAS‐ or STING‐deficiency. Utilizing a protein pulldown approach, we further demonstrate direct binding of D‐ODN to cGAS. Induction of a type I IFN response by D‐ODN was confirmed in human primary monocytes and monocyte‐derived macrophages. These results are relevant to our understanding of self–nonself‐discrimination by cGAS and to the pharmacologic effects of ODN, which currently are investigated in clinical studies. Abstract : Cytosolic ODN induce type‐I interferons by activating the cGAS/STING signaling pathway. This signaling response is initiated by direct binding of D‐ODN, but not K‐ODN to cGAS, resulting in TLR9‐independent secretion of type‐I interferons.